A case study of teachers’ efforts towards learning problems in virtual EFL class during Covid-19 school closure - Muhammad Yani; Kamaluddin Yusra; Khusnul Khotimah (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
The Covid-19 has been deemed a global pandemic affecting almost all sectors, particularly in education. Learning activities have been forced to relocate virtually due to the school closure. This study aimed at exploring teaching-learning problems felt by English teachers and their efforts to overcome those problems during the school closure in a state senior high school in West Lombok. Designed in a case study, two English teachers were voluntarily recruited using convenience sampling. The data for this study were gathered from observation, interviews, and documentation. Informed by the theory of Community of Inquiry (CoI) and previous empirical studies, the data were analysed using four stages of the interactive model. The investigation revealed that during the virtual teaching, teachers experienced considerable internal and external pedagogical glitches. It was also uncovered that the teachers disclosed some endeavours to maintain teaching, social, and cognitive presence in the instruction to surmount the nested pedagogical problems. However, their efforts were observed inadequate and left some room for improvement on how teachers could effectively serve in the virtual pedagogical practices. Some implications and future research directions are discussed accordingly. DOI: 10.26905/enjourme.v6i2.6463